Breast Cancer Focusing Tumor Microenvironment, Stem cells and Metastasis - Gunduz, Mehmet; Gunduz, Esra (IntechOpen, 2011)
Cancer is the leading cause of death in most countries and its consequences result in huge economic, social and psychological burden. Breast cancer is the most frequently diagnosed cancer type and the leading cause of cancer death among females. In this book, we discussed characteristics of breast cancer cell, role of microenvironment, stem cells and metastasis for this deadly cancer. We hope that this book will contribute to the development of novel diagnostic as well as therapeutic approaches.